Treatment Outcome of Subthreshold Micropulse Green Laser SMGL (532 nm) in Chronic Central Serous Chorioretinopathy - Joshi, Ichhya; Agarwal, Lalit; Aditya, Kshitij; Pradhan, Deepti; Prasad, Archana Kumari (Nepalese Journal of Ophthalmology, 2024)
Introduction: Subthreshold micropulse green laser (532nm) is effective for treatment of chronic CSCR with promising results. Objectives: To assess the treatment outcome of a single session subthreshold micropulse green laser (SMGL) 532nm in chronic central serous chorioretinopathy (CSCR). Methods: This was a prospective noncomparative consecutive case series. Eyes with chronic CSCR were treated with SMGL and evaluated at 1- and 3-months post laser. Best Corrected Visual Acuity (BCVA) and Central Macular Thickness (CMT), and Subretinal Fluid Height (SFR) following laser were evaluated. Results: A total of 16 eyes of 13 patients with the diagnosis of chronic CSCR were enrolled in this study. The mean age of the patients was 45 years (range 31-60 years). All of the patients had a history of CSCR of more than 4 months duration (mean 7.9 months ± 3.01). The median baseline BCVA was 0.4 log MAR which improved to 0.25 log MAR. Of the 16 eyes, 1 eye had 3 lines of improvement (6.25%), 4 eyes had 2 lines of improvement (25%), and 3 eyes had 1 line of improvement (18.75%) and 8 eyes-maintained vision (50%). The mean SRF height pre and post laser was 191.813 µm and 54.93 µm, respectively (P<0.001). Similarly, the mean CMT pre and post laser was 328.18 µm and 242.87 µm, respectively (P<0.009). There was complete resolution of PED in 3 out of 5 eyes (60%). Conclusion: Subthreshold micropulse green laser (532nm) is effective for treatment of chronic CSCR with promising results.